Peningkatan Keterampilan Public Speaking dan Etika Komunikasi Bagi Pengurus dan Anggota Tim Penggerak PKK (Pendidikan Kesejahteraan Keluarga) se Kota Medan - Nina Siti Salmaniah Siregar; Nadra Ideyani Vita; Warsani Purnama Sari (Universitas Medan Area, 2022)
Effective Communication Skills or known as public speaking skills or public speaking are skills that aim to inform messages, persuade or persuade, and entertain the audience at this time become one of the requirements that must be possessed by people in charge of providing services to others This community service is to increase the knowledge and readiness of the members and administrators of the Medan City PKK Mobilization Team to be reliable in carrying out public speaking activities and to increase understanding of communication ethics for the Medan City PKK Mobilizing Team reliable in carrying out public activities speaking / speaking in public. Thus, the quality of the management and members of the PKK team in Medan City in carrying out communication activities to the community can be carried out in a good, ethical and professional manner. There are many benefits that can be obtained by improving Effective Communication and Public Speaking skills, including; increase credibility, improve leadership skills, make it easier to convey ideas and ideas, reach extensive networking and can increase self-capacity in career and when dealing with other people on duty.